STATE AND TRENDS OF TABLE BEET PRODUCTION IN THE CONDITIONS OF EUROPEAN INTEGRATION - Басюк, Снижана (SWorldJournal, 2022)
In Ukraine, the vegetable industry during the long period of reforming the agricultural sector of the economy has undergone significant changes in the volume and structure of production. The current state and tendencies of development of table beet cultiv